Effect of peritoneal fluid on early embryonic development - Noordin, Liza; San, Gregory Tan Jin; Othman, Mohd. Shukri (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
The aetiology of endometriosis associated with infertility remains poorly understood. In recent years, the potential influence of peritoneal fluid (PF) or its cellular components have been proposed as possible mediators of infertility in endometriosis through it toxic effects on pre-implantation embryo. Several factors have been identified as embryotoxic factors, however, the mechanism of embryotoxicity have not well clarified. Studies were therefore undertaken to clarify the possible mechanisms of embryotoxicity in endometriosis and to determine the possible embryotoxic factor(s) that involved in the process. The role of exogenous nutrient (pyruvate) has also been examined in reducing or eliminating the embryotoxicity. Peritoneal fluid was collected from infertile women at reproductive age with 21 endometriosis (PF-E) (7 minimal or mild, 7 moderate, 7 severe) and 7 without endometriosis (PF-NE). Addition of PF-E to the culture medium from all stages of endometriosis significantly suppressed the mouse embryo growth at all stages of development, at 24, 48 and 72 hours, which correlated with the severity of the disease, as compared to control (no peritoneal fluid). Excessive pyruvate was able to reduce the embryotoxicity at all stages of development in minimal or mild and moderate PF-E, and only during the first 24 hours in severe PF-E. The level of IL-6 concentration was significantly higher in PF-E as compared to PF-NE and correlated with the severity of the disease. However, no significant difference was noted in the level of IL-8 between the two groups. Both interleukins were found to be embryotoxic with IL-6 is more potent. A positive correlation between the levels of IL-6 and its embryotoxicity was noted. These findings propose embryotoxicity to be a possible mechanism of infertility in endometriosis and the growth promoting effects of pyruvate indicated the mechanism of embryotoxicity might involve functional disruption of the intermediary metabolism such that excessive pyruvate is required to maintain embryo growth. Vl